Development of an indirect competitive enzyme-linked immunosorbent assay and immunochromatographic assay for hydrocortisone residues in milk. Issue 3 (4th May 2017) - Wang, Zhongxing; Xie, Zhengjun; Cui, Gang; Liu, Liqiang; Song, Shanshan; Kuang, Hua; Xu, Chuanlai
ABSTRACT: An anti-hydrocortisone (HDS) monoclonal antibody, 2G8, based on a HDS succinic anhydride derivative hapten, was prepared and used to develop an indirect competitive enzyme-linked immunosorbent assay (ic-ELISA) and an immunochromatographic assay for the detection of HDS in milk samples. The half inhibitory concentration (IC50 ) of the antibody was 0.095 ng/mL, its limit of detection was 0.013 ng/mL, its linear range of detection was 0.026–0.356 ng/mL, and its cross-reactivity with HDS analogs was <5%. In spiked samples and a recovery test, the recovery rates ranged from 92% to 98.5%, indicating the suitability of this ic-ELISA for the analysis of HDS in milk. The immunochromatographic strip had a cutoff value of 2 ng/mL in milk and could be used for the semiquantitative analysis of HDS. When milk samples were added to the sample pad of the strip, a bright test line indicated <0.2 ng/mL HDS, a weak test line indicated 0.2–2 ng/mL HDS, and no test line indicated ≥2 ng/mL HDS. Analysis of HDS in milk samples showed that results acquired by the immunochromatographic assay agreed well with results acquired by ic-ELISA. Thus, the ic-ELISA and strip assay developed in this study rapidly and sensitively detect HDS residues in milk samples.